The Use of Kinetic Sand Media to Improve the Initial Writing Ability of Disabled Students - Hartanti, Herma Raidha; Pratama, Toni Yudha; Utami, Yuni Tanjung (Widyagogik, 2025)
This study aimed to determine the effectiveness of using kinetic sand media as an intervention tool to improve the initial writing skills, specifically graphomotor control and letter imitation, in students with Intellectual Disabilities (ID) at SKh Negeri 02 Lebak. The research employed a quantitative pre-experimental design using the One Group Pre-test Post-test design. The subjects consisted of three students with intellectual disabilities (N=3) from the SDLB level. Data were collected through observation checklists (pre-test and post-test) and analyzed using the non-parametric Wilcoxon Signed Rank Test, appropriate for a small sample size. The analysis revealed a significant increase in the subjects’ initial writing scores following the kinetic sand intervention. The statistical test yielded an Asymp. Sig. (2-tailed) value of p 0.05, indicating a significant difference between pre-test and post-test scores. This result substantiates that the sensory and manipulative nature of kinetic sand successfully strengthened the subjects' intrinsic hand muscles and enhanced fine motor control necessary for writing. It is concluded that the use of kinetic sand media has a positive and statistically significant effect on improving the initial writing skills of students with intellectual disabilities. The intervention is highly recommended for special education settings as an engaging and effective pre-writing preparatory activity.